Hybrid Educational Didactics: The Villaverde Cave Anthropology and Archaeology Campus - Pérez Amores, Grecy; López Guerrero, Rosa; Zelaya Álvarez, Silvia Cristina (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
The primary aim of this didactic proposal, centred on learning by doing, was to unify anthropological and archaeological experiences within a collaborative and interdisciplinary project designed to foster critical thinking. To achieve this, we employed hybrid and plural methodologies that allowed students to engage with heritage-based learning, applying classroom concepts in a practical context. The project stemmed from the need for an ethnographic and archaeological study exploring the relationship between the past and present of Fuerteventura’s inhabitants, connected to a significant archaeological site for the local community.